Luca [videorecording (DVD)] - Romer, Dan (Disney/Pixar, 2021)
Set in a seaside town on the Italian Riviera, a young boy experiences an unforgettable summer. Luca shares his amazing adventures with his newfound friend Alberto, but their fun is threatened by a deeply held secret: they're sea monsters from another world just below the water's surface.